IMPLIKASI KARAKTERISTIK BUDAYA MASYARAKAT DALAM PENGELOLAAN HUTAN LINDUNG GUNUNG SIRIMAU KOTA AMBON PROVINSI MALUKU - Parera, Evelin; Purwanto, Ris Hadi; Permadi, Dwiko Budi; Sumardi, Sumardi (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This study examines the cultural characteristics of communities living around the Sirimau Protected Forest and their impact on sustainable forest management. The surrounding indigenous communities hold a deeply rooted cultural system that includes language, knowledge systems, social organization, technology, livelihoods, and religious beliefs, all of which influence their approach to natural resource management. One of the core elements is local ecological knowledge—an understanding of the forest’s ecosystem, flora, fauna, and geography that has been passed down through generations. Key social structures, such as the roles of local leaders (raja), community councils (saniri), and forest guardians (kewang), play a significant role in ecological stewardship through customary regulations, including the sasi tradition, which restricts forest use during specific periods to prevent overexploitation. The research emphasizes the importance of involving indigenous communities in forest management decision-making processes, which not only supports ecosystem sustainability but also preserves the cultural identity and values of these communities. Findings from this study advocate for community-based forest management approaches that integrate social, economic, and cultural aspects to achieve optimal environmental sustainability.